P847 Insomnia is common in IBD and associated with increased disability and abdominal pain. (30th January 2023) - Barnes, A; Andrews, J; Bryant, R V; Mountifield, R
Abstract: Background: Insomnia is common in those with chronic medical conditions. Insomnia is associated with decreased quality of life and is readily treatable through cognitive behavioural therapy for insomnia (CBTi). This study aimed to describe the associations with insomnia in an IBD population and its relationship with IBD related disability. Methods: An online questionnaire was administered through three tertiary IBD centres, social media and through a patient advocacy group (Crohn's Colitis Australia). The questionnaire included the insomnia index severity (ISI), a validated assessment of insomnia and its severity, with a score over 14 considered clinically significant insomnia. Validated measures of anxiety (GAD-7), depression (PHQ-9), physical activity (sIPAQ), and disability (IBD-DI-SR) were also utilised. IBD activity was assessed clinical IBD activity scores (HBI or SCCAI). Results: There were 670 responses included in the analysis. Median age was 41 years (32-70), with the majority being female (78%), and 57% having Crohn's disease. The mean disease duration was 11.9 years (10.4), 30% had undergone surgery for IBD and around half were on biologics (50.5%). The mean ISI score was 12.7 (6.09). Over a third of the cohort had at least moderate insomnia (ISI>15). A one-way ANOVA revealed differences in disability scores (IBD-DI-SR) (see table 1) between insomnia severity groups (F(3, 619) = 20.99, p < 0.001), with disability scores worsening with increasing severity of insomnia. Multivariable logistic regression analysis (see table 2) revealed that clinically significant insomnia was significantly associated with clinically active IBD, abdominal pain, clinically significant anxiety, and clinically significant depression. Conclusion: Insomnia is common in people with IBD with at least one third reporting moderate insomnia. Given that insomnia was associated with increased disability, consideration should be given for routine screening for insomnia in IBD patients. Mental health conditions and ongoing pain should be addressed with consideration given to referral for CBTi.